Assembly 2: respiratory intensive care. Issue 2 (June 2017) - Scala, Raffaele; Heunks, Leo; Gregoretti, Cesare; Schultz, Marcus J.; Dreher, Michael; Winck, João
Assembly 2, the home of groups "02.01: acute critical care" and "02.02: noninvasive ventilatory support", is a growing and active assembly within the European Respiratory Society (ERS). The number of members in Assembly 2 is steadily increasing, reaching a total of 846 in 2016. The members of Assembly 2 are young, with up to 40% of the members of Assembly 2 aged <40 years, and scientifically active, with 120 accepted abstracts at the recent ERS International Congress 2106 in London. The overarching aims of Assembly 2 are to promote respiratory intensive care within ERS through educational activities (in conjunction with HERMES (Harmonised Education in Respiratory Medicine for European Specialists)) and hands-on courses, to facilitate science within the field of respiratory intensive care, to disseminate the latest scientific novelties, to stimulate interactions among ERS members with interest in respiratory intensive care and to attract new ERS members. Meet @ERStalk Assembly 2: respiratory intensive care http://ow.ly/PnnB30b7nLU